Experience of implementating the rating system for assessing the knowledge of technical specialty students in teaching of "general chemistry - Asieieva, I. V. (Perfect Publishing, 2023)
The article considers the importance of quality training of future specialists in technical specialties in higher educational institutions. The peculiarities of the implementation of the rating system for assessing the knowledge and skills of students of technical specialties in the process of studying the discipline “General Chemistry” were analyzed. It was determined that the rating system, as a progressive method of monitoring knowledge, skills and abilities, creates conditions for students' motivation to education, activates cognitive activity and improves learning achievements. Attention is focused on the fact that the rating system for evaluating the quality of education is a successful replacement for traditional technologies of teaching students of technical specialties, but needs further improvement.
Keywords: educational process; higher professional education; educational and cognitive activity; students of technical specialties; knowledge control methods; rating system